2008
DOI: 10.1007/s10493-008-9128-z
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence for a novel Coxiella from Argas monolakensis (Acari: Argasidae) from Mono Lake, California, USA

Abstract: Argasid ticks are vectors of viral and bacterial agents of humans and animals. Recent reports indicate that some ornithophilic argasids harbored rickettsial agents. A Nearctic tick, Argas monolakensis Schwan, Corwin, Brown is ornithophilic and has not previously been examined for rickettsial agents. Thirty adult A. monolakensis were tested by PCR for DNA from Rickettsia or Coxiella. Amplicons from a Coxiella sp. that were divergent from Coxiella burnetii were detected in 16/30 A. monolakensis. These molecular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…In a recent study, Duron et al (2014) found molecular (Reeves, 2008), Ornithodoros capensis sensu lato group (Duron et al, 2014;Reeves et al, 2006;Wilkinson et al, 2014), O. rostratus (Almeida et al, 2012), Amblyomma americanum (Klyachko et al, 2007), A. cajennense (Machado-Ferreira et al, 2011) and A. loculosum (Wilkinson et al, 2014). However, all Coxiella strains found in these tick species are divergent from C. burnetii, the causative agent of Q fever, and may behave as endosymbionts (Duron et al, 2014).…”
Section: Bacterial Agentsmentioning
confidence: 99%
“…In a recent study, Duron et al (2014) found molecular (Reeves, 2008), Ornithodoros capensis sensu lato group (Duron et al, 2014;Reeves et al, 2006;Wilkinson et al, 2014), O. rostratus (Almeida et al, 2012), Amblyomma americanum (Klyachko et al, 2007), A. cajennense (Machado-Ferreira et al, 2011) and A. loculosum (Wilkinson et al, 2014). However, all Coxiella strains found in these tick species are divergent from C. burnetii, the causative agent of Q fever, and may behave as endosymbionts (Duron et al, 2014).…”
Section: Bacterial Agentsmentioning
confidence: 99%
“…These endosymbionts have been found in a variety of ticks species, including Haemaphysalis (Lee et al 2004, Ahantarig et al 2011, Arthan et al 2015), Amblyomma (Klyachko et al 2007, Machado-Ferreira et al 2011), Rhipicephalus (Bernasconi et al 2002), Ixodes (Kurtti et al 2002), Ornithodoros (Almeida et al 2012, Duron et al 2014), and Argas (Reeves 2008). The most recent study based on multilocus sequence analysis of a few housekeeping genes demonstrated that all Coxiella strains cluster into four highly divergent clades, suggesting that C. burnetii evolved from a tick endosymbiont (Duron et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…To date, various Coxiella-like microorganisms have been detected in both hard and soft ticks (21,32,33,34,35,36,37,38). Interestingly, Coxiella-like microorganisms exhibited diverse 16S rRNA genotypes from different tick species.…”
mentioning
confidence: 99%